2018
DOI: 10.1021/acs.biochem.8b00534
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity within a Family of Bacterial Phosphothreonine Lyases

Abstract: Phosphothreonine lyases are bacterial effector proteins secreted into host cells to facilitate the infection process. This enzyme family catalyzes an irreversible elimination reaction that converts phosphothreonine or phosphoserine to dehydrobutyrine or dehydroalanine, respectively. Herein, we report a study of substrate selectivity for each of the four known phosphothreonine lyases. This was accomplished using a combination of mass spectrometry and enzyme kinetics assays for a series of phosphorylated peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…The bacterial pathogen pThr lyases SpvC and OspF catalyze phosphate elimination from mitogen activated protein kinase (MAPK) activation loop peptides containing pThr to form the corresponding Dhb-containing peptides (Chambers et al, 2018;Zhu et al, 2007). We therefore used these lyases to mimic such pathogen-induced damage to prepare model, Dhb-containing peptides corresponding to the activation loops of ERK and Akt (Figure 2A; Figure S1C).…”
Section: Lancls Add Gsh To Dehydroamino Acids In Peptides Corresponding To Kinase Activation Loopsmentioning
confidence: 99%
“…The bacterial pathogen pThr lyases SpvC and OspF catalyze phosphate elimination from mitogen activated protein kinase (MAPK) activation loop peptides containing pThr to form the corresponding Dhb-containing peptides (Chambers et al, 2018;Zhu et al, 2007). We therefore used these lyases to mimic such pathogen-induced damage to prepare model, Dhb-containing peptides corresponding to the activation loops of ERK and Akt (Figure 2A; Figure S1C).…”
Section: Lancls Add Gsh To Dehydroamino Acids In Peptides Corresponding To Kinase Activation Loopsmentioning
confidence: 99%
“…Currently, the only confirmed mammalian targets of bacterial phospholyases are MAP kinases, including ERK1/2. Our prior work implied that phospholyases may have additional targets outside of the MAPK family . Moreover, this work has serendipitously identified histone H3 as a previously undiscovered target of OspF (Figure S7).…”
Section: Figurementioning
confidence: 78%
“…Previous work has established that, during bacterial infection, phospholyases attenuate the innate immune response by deactivating mitogen‐activated protein kinase (MAPK) signaling through β‐elimination of phosphate from a key pThr within the ERK1/2 activation loop –. Our recent work has demonstrated that phospholyases may have additional targets beyond the MAPK family . Identification of new phospholyase targets would lead to a better understanding of the infection process, and could uncover valuable biomarkers for bacterial infection.…”
Section: Figurementioning
confidence: 99%
“… 10 Using an in vitro LC-MS assay that measured the conversion of p-Thr and p-Ser containing peptides to the respective dehydroamino acids, it was possible to assess the substrate specificity of several bacterial phospholyases. 11 This work suggested that the promiscuous phospholyase activity of OspF may be responsible for the increased pathogenicity of Shigella compared to other bacteria such as Salmonella .…”
Section: Dehydroamino Acids In Naturementioning
confidence: 95%